2018
DOI: 10.1186/s12875-018-0744-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring current and potential roles of Australian community pharmacists in gout management: a qualitative study

Abstract: BackgroundGout is an increasingly prevalent form of inflammatory arthritis. Although effective treatments for gout exist, current management is suboptimal due to low medication adherence rates and treatments that are non-concordant with guidelines. Medications are the mainstay and most effective form of gout management. Thus, there is potential for community pharmacists to play an important primary health care role in gout management, however their current role and their potential to improve management of gout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…It is not viewed seriously as a form of inflammatory arthritis. Consequently, gout is considered a minor health condition and is being inappropriately treated as only an acute episodic condition rather than one requiring chronic ongoing treatment 34–36. These themes were also shown in our study when patients considered gout to be unremarkable compared with their other health conditions.…”
Section: Discussionsupporting
confidence: 61%
“…It is not viewed seriously as a form of inflammatory arthritis. Consequently, gout is considered a minor health condition and is being inappropriately treated as only an acute episodic condition rather than one requiring chronic ongoing treatment 34–36. These themes were also shown in our study when patients considered gout to be unremarkable compared with their other health conditions.…”
Section: Discussionsupporting
confidence: 61%
“…Although this prior study lacked a control group and relied on self-reports of adherence, these results suggest that a more intensive intervention -one that integrates patient education with regular in-person patient-provider interactions -could lead to greater and more durable improvements in adherence and outcomes. The potential importance of integrating patient education is further highlighted in reports demonstrating that gout-specific knowledge deficits (common among gout sufferers) might be amenable to relatively simple educational interventions delivered in part or wholly by non-physician providers such as pharmacists 34,35 . It is possible that a more resource-intensive strategy such as that described by Rees et al could be deployed in a stepwise, escalating fashion only after the failure of a less intensive (and more scalable) intervention (such as the one described in this study, delivered to 681 patients by a single half-time pharmacist).…”
Section: Discussionmentioning
confidence: 99%
“…Doherty, et al 21 have shown outstanding effect on attainment and maintenance of target SU of close supervision of patients with gout receiving ULT by trained nurses, but resourcing this approach on a large scale is challenging. Pharmacists, who are often well-placed to monitor medication adherence, offer a potentially cost-effective approach to improving outcomes for patients 22,23 .…”
Section: Predictors Of Success In Gout Treatmentmentioning
confidence: 99%